Enhancing Teaching and Learning through Digital Storytelling: Exploring Elementary Teachers' Perspectives and Challenges in Hiroshima Prefecture - Setyaningsih Rachmania; Bachrudin Musthafa; Sri Setyarini; Iyen Nurlaelawati; Takamichi Asakura; Nissa Aulia Belistiana Utami (Information Technology Education Journal, 2026)
Purpose – This study addresses what we term the "Pedagogical Infrastructure Gap" is a condition in which educational institutions have successfully deployed digital hardware and devices through government-led initiatives while neglecting to equip teachers with the pedagogical vocabulary required to theorize their own instructional practices. Method – Employing a descriptive qualitative approach, data were collected from four in-service teachers currently pursuing postgraduate studies at Hiroshima University through semi-structured interviews and document analysis. Findings – Some of the participants actively employ multimodal and narrative-based pedagogical practices that implicit DST-related to identify or articulate their work within that conceptual framework. Implications – This study emphases the untapped pedagogical potential embedded within these implicit practices and recommends professionally-oriented interventions focused on "naming the practice" that is, on bridging the gap between what teachers already do and what they can consciously leverage through theoretical awareness. Originality – Unlike the majority of existing studies, which examine outcomes in contexts where teachers are deliberately trained in Digital Storytelling (DST), this research is uniquely positioned to document how educators accidentally arrive at Digital Storytelling (DST) through independent experimentation with multimodal tools such as iMovie and PowerPoint, thereby contributing an underexplored perspective to the global literature on ICT integration in elementary education.